Antioxidant properties of mistletoe Globimetula braunii - Jamil, Shajarahtunnur (2015)
Globimetula braunii (Engler) Van Tiegh is called mistletoe belongs to Loranthaceae family. This plant is widely used in ethnomedicine for the management of diverse diseases by many tribes in Nigeria such as diabetes, hypertension, rheumatism, epilepsy, infertility, stomach problems and as a laxative. Phytochemical analysis and antioxidant evaluation were conducted on the leaves extracts of Globimetula braunii. The powdered leaves were successively extracted using cold extraction method with n-hexane, dichloromethane and methanol. Removal of the solvents using rotary evaporator gave dark gummy extracts. All these crude extracts were evaluated for antioxidant capacity measured using 2,2- diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethyl-benzothiazoline-6- sulphonic acid) or ABTS assays. The methanolic and n-hexane crude extracts of the leaves showed strong scavenging capacity with SC50 values of 2.82 µg/mL and 10.69 µg/mL respectively which are higher compared to the standard control butylated hydroxyanisole (SC50 = 11.30 µg/mL). The dichloromethane crude extract exhibited significant activity compared to the standard control with SC50 value of 18.48 µg/mL. The ABTS assay showed that the methanol crude extract has significant activity (SC50 value of 357.5 µg/mL) compared to standard controls butylated hydroxyanisole and Trolox (SC50 values of 317.7 µg/mL and 354.0 µg/mL respectively). The n-hexane and dicholormethane crude extracts exhibited weak scavenging capacity in the ABTS assay with SC50 values of 918.8µg/ml and 1603 µg/mL respectively. The phytochemical analysis revealed the presence of saponins, carbohydrates, flavonoids, tannins, anthraquinones and steroids in the leaves extracts.